The Use OF Analytical Hierarchy Process (AHP) In Product Development Process - Hambali, Arif; Ab. Rahman , Mahmood; Isa, Halim (2013)
The use of the analytical hierarchy process (AHP) in the product development process was explored in this paper. AHP is a decision-making method has been widely used for more than 20 years recently and it has also been used in product development activities. Related articles around the years 2002 to 2012 were identified to review the implementation of the AHP methodology in product development activities. The use of AHP is not only limited to the AHP itself but can be integrated with other design tools. This paper shows the AHP applications and its integration in product development activities. The framework was developed to describe the relationship AHP with the other design tools in the product development activities. Therefore, it may be used to help decision makers to select the appropriate design tool in the area of product development which enhance the AHP applications in the product development activities.